Humaniora Scientia - Humaniora Scientia (Humaniora Scientia, 2020)
Humaniora Scientia online journal of Linguistics, Literature and Translation is published by the English Department of Catholic University of Widya Mandala Madiun. It is published twice in a year, every March and September. This journal accepts any research on linguistics, literature and translation. It is also possible for language teaching research to be included into the journal. Humaniora Scientia is indexed by Google Schoolar.